Investigating Teachers' Perceptions, Challenges, and Support Systems in Handling a Visually Impaired Student in a Teacher Education Institution - Antonio, Vida V.; Dela Cruz, Andrian D. (Future Science / FSH-PH Publications, 2025)
Inclusive Education (IE) is a recognized right mandated by international and Philippine policies, requiring schools to accommodate learners with disabilities, including those with visual impairment (VI). Teachers play a vital role in implementing IE, yet their readiness, perceptions, and access to support systems shape the effectiveness of inclusive practices. This study aimed to investigate teachers’ perceptions, challenges, and support systems in handling a student with VI in a Teacher Education Institution (TEI) in northern Philippines. A qualitative-descriptive case study design was employed, involving 12 purposively selected teachers who had taught the student with VI in at least one semester. Data were gathered through semi-structured interviews and focus group discussions and analyzed thematically using Braun and Clarke’s (2012) framework. Ethical protocols such as informed consent and confidentiality were strictly observed. Findings revealed that teachers strongly valued inclusive education and emphasized empathy, patience, adaptability, and learner-centered approaches in teaching students with VI. They adopted flexible strategies such as tactile resources, auditory cues, and differentiated instruction. However, challenges included limited training in Braille and inclusive pedagogy, lack of accessible resources, barriers in assessment, and difficulties in creating safe and inclusive classroom environments. Despite these, teachers received support through collegial collaboration, peer assistance, expert guidance from SPED teachers and ECSNED department staff, family involvement, access to assistive technologies, and institutional measures such as inclusive classroom setups and alternative assessments. In conclusion, teachers demonstrated commitment and creativity in promoting inclusion but faced systemic gaps in preparation and resources. t.